Technology Entrepreneurship (ENT600) : Adidas Group / Nursyamimi Muhamad Fauzi - Muhamad Fauzi, Nursyamimi (2021)
The purpose of this study is to identify the problem of the product and improve it to be a better product. I got the opportunity to research a company which manufactured the same product that I want to develop, which is Adidas company. This company is currently based in Germany where Adolf Dassler is the founded the business in 1924 and successfully expanded to over 350 brand-stores branches in the country all around the world such as Germany, Australia, Canada, India, Korea, Mexico, Poland, Romania, South Africa, Sweden, Turkey etc. It was the largest sportwear manufacturer in Europe and the product are traditionally marked with three-striped trademark. The strength, weakness opportunities and threats of the company in real business world was analysed by using SWOT analysis. Thus, from the needs and demands from the existing consumers of this company was identified. There is a lot of problems regarding this issue. The main issue will be from this backpack is it lack the security as it does not secure the things inside the backpack. Moreover, the material that are used is less tough and easily absorb water. Furthermore, the colour of the product is limited and do not have many choices. The backpack also does not have more pockets as needed and the design is the same as the other brands. Then, the problems was analysed and the solution was fine to overcome and to fulfil their needs and making it as our innovation to be continued in new Product Development task. Various solution or idea was implemented to solve the issue. Every problems contain more than one ideas of improvement to make the product perfect and outstanding. Next, one of the ideas was chosen as the best solution. Firstly, the security problem of the backpack was solved by invented built-in biometric fingerprint sensor to the zipper. PVC coated polyester material was used because it is good waterproof material thus can protect the bag from being wet. Various choices of colour were added to make it look more attractive and enhance the buyers’ interest on that product. The backpack was provided with more pockets and features such as shoulder strap pockets, USB ports and LED light to make the product more reliable and productive so that it can fulfil consumers criteria for their ideal backpack.